1994
DOI: 10.1159/000178201
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Aggregation and Microcirculation in Rat Cremaster Muscle

Abstract: Using intravital microscopy of the rat cremaster muscle, we studied the effects of changing red blood cell (RBC) aggregation on RBC arteriolar velocity and perfused capillary density (PCD). To modify RBC aggregation, 2 and/or 10% dextran (molecular weights 40,000, 70,000 or 480,000) or fresh rat plasma was infused into adult male rats via a normovolemic hemodilution procedure. The high-molecular-weight dextrans (70,000 and 480,000) both induced RBC hyperaggregation associated with similar dose-dependent decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 18 publications
4
25
0
Order By: Relevance
“…This phenomenon was known since long ago, but the relationship between the RBCs aggregation (as cause) and the increase of resistance disturbing the flow (as result) in microvessels was difficult to prove convincingly because some inevitable factors, such as the pressure gradient and/or the microvascular diameter changes, could always be involved in the living microvascular networks. The effect of the RBCs aggregation on blood flow was largely examined by infusing macromolecules, preferably dextran with high molecular weight, into isolated organs [60][61][62] and in patients with serum hyperviscosity syndrome [63,64]. Under these conditions it was difficult to prove whether the increased flow resistance was due to the RBCs aggregation itself or to the increased plasma viscosity.…”
Section: Rbcs Aggregation As a Factor Inevitably Disturbing Blood Flomentioning
confidence: 99%
“…This phenomenon was known since long ago, but the relationship between the RBCs aggregation (as cause) and the increase of resistance disturbing the flow (as result) in microvessels was difficult to prove convincingly because some inevitable factors, such as the pressure gradient and/or the microvascular diameter changes, could always be involved in the living microvascular networks. The effect of the RBCs aggregation on blood flow was largely examined by infusing macromolecules, preferably dextran with high molecular weight, into isolated organs [60][61][62] and in patients with serum hyperviscosity syndrome [63,64]. Under these conditions it was difficult to prove whether the increased flow resistance was due to the RBCs aggregation itself or to the increased plasma viscosity.…”
Section: Rbcs Aggregation As a Factor Inevitably Disturbing Blood Flomentioning
confidence: 99%
“…Mchedlishvili et al (19) found that administration of Dextran 500 reduced the FCD in the rabbit cerebral cortex dramatically, from ϳ90% to ϳ10%. Vicaut et al (32,33) also found substantial reductions (Ͼ30%) in FCD in rat hearts and cremaster muscle after the infusion of Dextran 480. Both studies indicated that red blood cell aggregation can reduce FCD to a level that would increase the diffusion distance for nutrients and waste products and reduce available surface area for exchange of fluid and solutes.…”
mentioning
confidence: 90%
“…In vivo experiments using glutaraidehvde (or formaldehyde)-treated erythrocytes have shown the increased flow resis tance in the microvascular network [10][11][12], On the other hand, the physiological influence of erythrocyte aggrega tion on systemic circulation has also been examined in vivo by injecting various macromolecules such as dextrans. However, it is controversial whether the increased viscosity and thus the increased flow resistance is due to the erythrocyte aggregation itself or to the increased plas ma viscosity [13][14][15][16][17],…”
Section: Introductionmentioning
confidence: 99%